Stochastic approach to the smart quantum confinement model in porous silicon - Ramírez Porras, Arturo (2002)
A model that encompasses two approaches to explain the photoluminescence in p-type porous silicon is proposed. The model considers a stochastic distribution of nanocrystallite sizes within the porous matrix and explain the luminescence emission of air-exposed specimens in terms of the presence of Si=O and Si=H bonds. Fitting of experimental data is performed to extract size-related statistical parameters. The results are in good agreement with the band-to-band and localized state-to-band transition theoretical framework.